Progress in mechanistically novel treatments for schizophrenia. Issue 9 (29th June 2021) - Neef, James; Palacios, Daniel S.
Abstract : Recent efforts to identify small molecules for schizophrenia with non-D2 mechanisms will be highlighted. The potential for disease modifying treatments for schizophrenia will also be discussed. Abstract : Currently available pharmacological treatments for schizophrenia derive their activity mainly by directly modulating the D2 receptor. This mode of action can alleviate the positive symptoms of schizophrenia but do not address the negative or cognitive symptoms of the disease and carry a heavy side effect burden that leads to high levels of patient non-compliance. Novel mechanisms to treat the positive symptoms of schizophrenia with improved tolerability, as well as medicines to treat negative and cognitive symptoms are urgently required. Recent efforts to identify small molecules for schizophrenia with non-D2 mechanisms will be highlighted, with a focus on those that have reached clinical development. Finally, the potential for disease modifying treatments for schizophrenia will also be discussed.